PENERAPAN METODE PENGAKUAN KEUNTUNGAN PEMBIAYAAN MURABAHAH (AT TAMWIL BI AL MURABAHAH) PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2013 - ISTIKOMA, NURUL (Jurnal Akuntansi AKUNESA, 2014)
This research is aimed to determine the implementation of profit recognation method ofmurabahah financing in Islamic Banks in Indonesia based on annual report year 2013. Theresearch method used is descriptive and used secondary data such as Islamic Bank’s annualreport year 2013 . The result of this research shows that Islamic Banks in Indonesia applieddifferent method to recognize the profit of murabahah financing, but the implementation isstill in accordance with applicable regulation. Differences in the recognation of profit basedon murabahah contract completion period. Annuity method is applied to murabahah withdeffered payment period of one year or one period and proportionate methodis applied tomurabahah with deffered payment period more than one year or one period.Keyword : profit recognation, financing, Murabahah, Islamic Banks